Correction: Acupuncture decreased the risk of stroke among patients with fibromyalgia in Taiwan: A nationwide matched cohort study. - Ming-Cheng Huang; Hung-Rong Yen; Cheng-Li Lin; Yu-Chen Lee; Mao-Feng Sun; Mei-Yao Wu (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0239703.].